How Far Away Are Lithium-Sulfur Batteries From Commercialization? - Zhu, Kunlei; Wang, Chao; Chi, Zixiang; Ke, Fei; Yang, Yang; Wang, Anbang; Wang, Weikun; Miao, Lixiao (Frontiers in Energy Research, 2019)
With the increasing demand for green energy due to environmental issues, developing batteries with high energy density is of great importance. Li-S batteries, since their big breakthrough in 2009, have attracted much attention in both academia and industry. In academia, significant progress has been made in improving the specific capacity, rate capacity, and cycle performance using various novel strategies. However, the performance is hugely different when these strategies are extended to mass production, indicating a significant difference between academic research, and industrial production. In this brief review, we discussed the gap between the academic research and commercialization in detail based on literature reports and to our more than 10 years' experience on Li-S pouch cells, which including cathodes, anodes, separators, interlayers, electrolytes, and additives. The problems, which existing in pouch cells by using the materials and technologies developed by academic research using coin cells, was analyzed. We expected that this review could be helpful to both academic research and industrial commercialization of Li-S batteries.